Management of resources in muslim countries and communities : challenges and prospects - Ibrahim, Hassan Ahmed (IIUM Press, 2012)
Management of Resources in Muslim Countries and Communities: Challenges and Prospects comprises a selected papers that were presented in a recent conference organised by the International Institute of Muslim Unity (IIMU) of the International Islamic University Malaysia (IIUM). Despite the fact that the Muslim world is blessed with enormous natural resources like: fertile lands, water, gold, oil, uranium, minerals and hard working masses, a vast majority of Muslim countries have yet to deliver the goods to their people. It is for this main reason that the conference focused on resource management in the Muslim world and critically examined the performance in this area and aimed at making appropriate recommendations to meet the challenges facing the Muslim ummah in the 21st century. The conference explored the issues pertaining to the utilization of resources and identified the ways and means to put them into good and efficient use. It is a known fact that these resources namely, material (e.g., petroleum, gas, gold, timber, etc), financial and human are aplenty in many of the Muslim countries. And yet, we find most of them have not been fully utilized. The major thrust of the conference was discussions and deliberations among the presenters and participants, who came from all over the world, on how to make effective and efficient usage of all kinds of resources in the Muslim countries.